2003
DOI: 10.1152/jn.00175.2003
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Induces Ectopic Mechanical Sensitivity in Axons of Nociceptors Innervating Deep Tissues

Abstract: A variety of seemingly diverse pain syndromes are characterized by movement-induced pain radiating in the distribution of a peripheral nerve or nerve root. This could be explained by the induction of ectopic mechanical sensitivity in intact sensory axons. Here we show that inflammation led to mechanical sensitivity of the axons of a subset of mechanically sensitive primary sensory neurons. Dorsal root recordings were made from 194 mechanically sensitive neurons that innervated deep and cutaneous structures and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
136
2
9

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(162 citation statements)
references
References 37 publications
15
136
2
9
Order By: Relevance
“…Under normal conditions, axons have not been reported to exhibit long-term, adaptive increases in excitability. However, mammalian sensory axons can display persistent hyperexcitability at sites of nerve injury (Zimmermann, 2001) and inflammation (Tal and Eliav, 1996;Eliav et al, 2001;Bove et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Under normal conditions, axons have not been reported to exhibit long-term, adaptive increases in excitability. However, mammalian sensory axons can display persistent hyperexcitability at sites of nerve injury (Zimmermann, 2001) and inflammation (Tal and Eliav, 1996;Eliav et al, 2001;Bove et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…7,8,16,19,22,35 Neurodynamic tests are considered to be able to detect increased nerve mechanosensitivity. 12,15,16,19,22,33 This heightened sensitivity in response to mechanical stimuli has been attributed to local inflammatory processes within the nerve 1,4,10,11,14,22 that are specifically related to its connective tissue. 32 When determining whether the result of a neurodynamic test is suggestive of increased nerve mechanosensitivity and therefore relevant to current patient complaints, it is important to consider several factors.…”
mentioning
confidence: 99%
“…22 Animal experiments have demonstrated that local nerve inflammation results in increased mechanical sensitivity of otherwise intact axons. 1 When a nerve is inflamed, minimal elongation ( 3%) or locally applied pressure can trigger ectopic impulse generation, 14 which may lead to the provocation of pain and other symptoms. Although these recent insights in pathophysiology Controlled laboratory study using single-group, within-subject comparisons.…”
mentioning
confidence: 99%